2014
DOI: 10.7567/jjap.54.01ag06
|View full text |Cite
|
Sign up to set email alerts
|

Effects of additional vapors on sterilization of microorganism spores with plasma-excited neutral gas

Abstract: Some fundamental experiments are carried out in order to develop a plasma process that will uniformly sterilize both the space and inner wall of the reactor chamber at atmospheric pressure. Air, oxygen, argon, and nitrogen are each used as the plasma source gas to which mixed vapors of water and ethanol at different ratios are added. The reactor chamber is remotely located from the plasma area and a metal mesh for eliminating charged particles is installed between them. Thus, only reactive neutral particles su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…23,24) The grounded stainless steel mesh was installed 200 mm downstream of the discharge area, which eliminated charged particles from the gas. 10) The gas that reached the reactor chamber was denoted as the plasma-excited neutral gas. The plasma-excited neutral gas had only comparatively long-life reactive neutrals such as plasma-excited molecules or radicals.…”
Section: Generating Plasma-excited Neutral Gasmentioning
confidence: 99%
See 1 more Smart Citation
“…23,24) The grounded stainless steel mesh was installed 200 mm downstream of the discharge area, which eliminated charged particles from the gas. 10) The gas that reached the reactor chamber was denoted as the plasma-excited neutral gas. The plasma-excited neutral gas had only comparatively long-life reactive neutrals such as plasma-excited molecules or radicals.…”
Section: Generating Plasma-excited Neutral Gasmentioning
confidence: 99%
“…[2][3][4][5][6][7][8][9] We previously examined a plasma process using plasmaexcited neutral gas that will uniformly sterilize both the space and inner wall of a reactor chamber. 10,11) Atmospheric pressure plasma was located remotely from the reactor chamber. Only reactive neutral species such as plasmaexcited gas molecules and radicals were separated from the plasma and sent to the reactor chamber.…”
Section: Introductionmentioning
confidence: 99%
“…perviridis. Furthermore, Matsui et al 10) also suggested that long-lifetime neutral particles in the gas phase, such as O 3 , H 2 O 2 , and HNO 3 , and synergistic effects between these species play a key role in the disinfection of Geobacillus stearothermophilus spores. To utilize the PTW effectively and efficiently, it is important to control the ROS= RNS concentration and to clarify the interaction between species in plasma and ROS=RNS in water as well as to investigate efficacy in the application fields, since PTW with a wide-ranging ROS=RNS concentration is used for the investigation of efficacy.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, many studies on plasma applications of agriculture and medicine have been reported. [1][2][3][4][5][6][7][8][9] In particular, effects of plasma irradiation on the germination and growth of plants have been investigated as agricultural applications. It has been reported that effects of plasmas using various gases such as CF 4 , aniline, cyclohexane, helium, and air on the germination and growth enhancement of plants are observed.…”
Section: Introductionmentioning
confidence: 99%